Unconventional T Cells’ Role in Cancer: Unlocking Their Hidden Potential to Guide Tumor Immunity and Therapy - Paola Pinco; Federica Facciotti (Cells)
Unconventional T (UC T) cells, including invariant natural killer T (iNKT) cells, mucosal-associated invariant T (MAIT) cells, γδ T cells, and double-negative (DN) T cells, are key players in immune surveillance and response due to their properties combining innate-like and adaptive-like features. These cells are widely present in mucosal tissues, where they can rapidly respond to infections and tumor-associated changes. In fact, UC T cells can have both pro- and anti-tumoral effects, with their activity influenced by factors such as microbial composition and the tumor microenvironment. In particular, intratumoral microbiota significantly impacts the development, function, and activation of UC T cells, influencing cytokine production and shaping the immune response in various cancers. The complex crosstalk between UC T cells and the surrounding factors is discussed in this review, with a focus on how these cells might be interesting candidates to explore and exploit as anticancer therapeutic agents. However, the great potential of UC T cells, not only demonstrated in the context of adoptive cell transfer, but also enhanced through techniques of engineering, is still flanked by different challenges, like the immunosuppressive tumor microenvironment and heterogeneity of target molecules associated with some specific categories of tumors, like gastrointestinal cancers.